Potentiometric study using chemically modified silica gel with pyridinium as membrane for ClO4 - ions - Lorencetti, Lilian L.; Gushikem, Yoshitaka; Kubota, Lauro T.; de Oliveira Neto, Graciliano; Fernandes, João Roberto [UNESP] (Springer Nature, 1995)
A potentiometric sensor for the perchlorate anion was developed by mixing chemically modified silicagel with pyridinium perchlorate, with an epoxy polymer and graphite. The electrode showed Nernstian response between 1.0 × 10-2 and 1.0 × 10-3M perchlorate concentrations. The electrode showed high selectivity to this ion at solutions pH between 5.5 and 8.0. The presence of IO4 -, NO3 -,Br-, IO3 -, Cl- and SO4 2- ions in the solutions, had only small interference in the electrode response in the range mentioned. © 1995 Springer-Verlag.
Keywords: modified silica gel; perchlorate analysis; perchlorate selective electrode; pyridinium ion